Fetal Environment and Glycosylation Status in Neonatal Cord Blood: A Comprehensive Mass Spectrometry-based Glycosylation Analysis. Issue 14 (April 2016) - Sato, Ryosuke; Tsuchiya, Kenji J.; Matsuzaki, Hideo; Takei, Nori; Itoh, Hiroaki; Kanayama, Naohiro; Suda, Takafumi; Watanabe, Hiroshi; Ohashi, Tetsu; Tanaka, Masakazu; Nishimura, Shin-Ichiro; Maekawa, Masato; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Fetal environment is known to be a major predictive factor of type 2 diabetes and cardiovascular disease. However, associations of fetal environment and cord blood glycoforms are uncertain. In this study, we aimed to determine whether glycosylation status in neonatal cord blood is associated with perinatal outcomes reflecting a poor fetal environment. Thirty-six low birth weight (LBW) infants and 120 normal birth weight infants were recruited from a longitudinal birth cohort. We conducted a comprehensive cord blood N-glycan analysis using matrix-assisted laser-desorption/ionization time-of-flight mass spectrometry. Associations of N-glycans with perinatal outcomes, including LBW, small for gestational age, and levels of cord blood leptin and adiponectin, were evaluated using logistic or multiple regression. We also prospectively explored correlations between N-glycans and 6 or 18-month rapid weight gain (>0.67 SD score). A total of 35 N-glycans were detected ( m/z value 1362.481–3865.407). Of these, abundance levels of G3414 ( m/z value 3414.238) were inversely correlated with LBW and small for gestational age. Abundance levels of G1915 ( m/z value 1914.698), G2744 ( m/z value 2743.994), G3049 ( m/z value 3049.105), and G3719 ( m/z value 3719.349) were inversely related to LBW. The total N-glycan abundance levels were strongly positively correlated with levels of leptin and adiponectin in cord blood. In a prospective exploratory analysis, the 5 LBW-related N-glycans (G1915, G2744, G3049, G3414, and G3719) were all inversely associated with 6 or 18-month rapid weight gain. These N-glycans are structurally categorized into 2 different categories: fucosylated bi or tri-antennary N-glycans; and tri or tetra-antennary N-glycans without fucosylation. In conclusion, mass spectrometry-based cord blood glycosylation analysis shows that 5 types of N-glycans are potential predictors of a poor fetal environment.